2023
DOI: 10.1113/jp283897
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement of cell types in the rat carotid body neurogenic niche induced by chronic intermittent hypoxia

Abstract: The carotid body (CB) is a prototypical acute oxygen (O2)‐sensing organ that mediates reflex hyperventilation and increased cardiac output in response to hypoxaemia. CB overactivation, secondary to the repeated stimulation produced by the recurrent episodes of intermittent hypoxia, is believed to contribute to the pathogenesis of sympathetic hyperactivity present in sleep apnoea patients. Although CB functional plasticity induced by chronic intermittent hypoxia (CIH) has been demonstrated, the underlying mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…Notably, the characteristics of Olfr78-deficient glomus cells resemble those of CB neuroblasts; these are immature glomus cell precursors that complete their maturation upon exposure to hypoxia. 17 , 40 Carotid body neuroblasts are weakly TH-positive and have reduced dopamine quantal content and poor secretory activity and responsiveness to hypoxia but maintain responses to other stimuli. In addition, their capacitance (proportional to cell size) is smaller than that of glomus cells and more than 80% of these cells exhibit large Na + currents, a sign of cellular immaturity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the characteristics of Olfr78-deficient glomus cells resemble those of CB neuroblasts; these are immature glomus cell precursors that complete their maturation upon exposure to hypoxia. 17 , 40 Carotid body neuroblasts are weakly TH-positive and have reduced dopamine quantal content and poor secretory activity and responsiveness to hypoxia but maintain responses to other stimuli. In addition, their capacitance (proportional to cell size) is smaller than that of glomus cells and more than 80% of these cells exhibit large Na + currents, a sign of cellular immaturity.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Remarkably, sympathetic activation and systemic hypertension induced by chronic intermittent hypoxia are reduced in constitutive Olfr78 knockout mice. 13 As that chronic intermittent hypoxia activates the conversion of CB neuroblasts into mature glomus cells, 40 an inhibition of this process could explain the decrease in sympathetic overactivation induced by intermittent hypoxia in constitutive (or global) Olfr78 knockout mice. 13 In closing, we speculate that Olfr78 inhibitors, with a tissue or organ action that is more restricted to the CB than HIF2α inhibitors, 48 , 49 may produce an attenuation of CB activity without entirely abolishing the life-saving responses to hypoxia and hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of the hypoxic microenvironment on mitochondria are dependent on the type of hypoxic environment 10 , 11 . In this experiment, we successfully simulated the acute, progressively resolving hypoxic environment by establishing an AFT model in nude mice and observed diminished mitochondrial respiratory function under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria, the organelles responsible for energy metabolism in mammalian cells, are extremely susceptible to and highly reliant on oxygen concentration to conduct physiological functions 8 , 9 . Studies have shown that mitochondria undergo different functional adaptations depending on the type of hypoxia 10 , 11 . On the one hand, the dramatic decrease in intracellular oxygen concentration inhibits oxidative phosphorylation (OXPHOS) in the mitochondria, resulting in a decrease in ATP production and, more importantly, high production of reactive oxygen species (ROS) in the cell, which can damage many organelles or macromolecules and ultimately threaten cell survival 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Caballero et al. (2023) found that CIH induces a slight increase in the CB volume, and mobilization of immature quiescent neuroblasts that enter a process of differentiation into mature chemoreceptor cells. In addition, they found that CIH enhances mitochondrial responsiveness to hypoxia in maturing neuroblasts as well as in chemoreceptor cells.…”
Section: Introductionmentioning
confidence: 99%